2009
DOI: 10.1213/ane.0b013e318194f3e6
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Report on the Prognostic Significance of Preoperative Brain Natriuretic Peptide and Postoperative Cardiac Troponin in Patients Undergoing Major Vascular Surgery

Abstract: These data suggest that measurement of preoperative BNP concentrations in addition to postoperative cTn concentrations provides additive prognostic information for MACE and mortality after major vascular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 27 publications
(21 reference statements)
0
42
0
5
Order By: Relevance
“…1). Fifty-seven studies were excluded, as we were unable to obtain sufficient data and the remaining nine studies, representing seven patient cohorts, were then eligible for analysis [2,[7][8][9][10][11][12][13][14]. An additional cohort was identified [15], resulting in eight cohorts included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…1). Fifty-seven studies were excluded, as we were unable to obtain sufficient data and the remaining nine studies, representing seven patient cohorts, were then eligible for analysis [2,[7][8][9][10][11][12][13][14]. An additional cohort was identified [15], resulting in eight cohorts included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Until recently, research was done in smaller cohorts of patients undergoing mainly vascular and other high-risk but elective surgical procedures, showing an incidence of postoperative myocardial injury of 8% to 52%. 4,12,13,[29][30][31][32][33][34][35][36][37][38][39] Studies with a follow-up time of 12 months found a 2-to 20-fold increased mortality risk. Studies including emergency surgery reported an incidence of 33% to 53% of postoperative myocardial injury and 4-to 12-fold increased mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining studies, three reported exclusively on patients undergoing emergency surgery, 38,45,48 and one documented both elective and emergency surgeries that were classified as being high risk. 46 Certain studies investigated outcomes in a specific surgical discipline, including thoracic surgery (4), 36,50,51,54 vascular (7), 29,40,42,44,55,57,59 orthopaedic (5), 45,[47][48][49]60 major abdominal (1), 56 oesophagectomy (1), 41 while the rest documented outcomes following a variety of surgeries performed (10), 34,35,[37][38][39]43,46,52,53,58 including a mix of general, head and neck, gynaecological, orthopaedic, vascular, urological, neurosurgery and thoracic surgery.…”
Section: Included Studiesmentioning
confidence: 99%
“…All of the included studies demonstrated that an elevated preoperative NP measurement was an independent predictor of the primary study outcome. 39 was a prospective derivation study with a subsequent validation study performed; one 44 was a prospective prespecified secondary analysis of a cohort in a placebo-controlled randomised controlled trial (RCT); one 45 was a cohort extracted from a prospective observational study; and one 54 was a retrospective review of patients enrolled in a different study with prospectively collected data.…”
Section: Association Between Nps and Postoperative Major Adverse Cardmentioning
confidence: 99%